DIAGNOSTIK AWAL PATOGEN FUNGI DI AREA PERMAKULTUR BUKIT KOR, TERENGGANU, MALAYSIA - Tarigan, Selvia Elsania Br.; Fadhillah, Wizni; Mohammed Sidique, Siti Nordahliawate (Fakultas Pertanian, Universitas Janabadra, 2024)
Permaculture is a type of agricultural system that requires a certain design process to make the agricultural system more sustainable. Plants in the permaculture area are attacked by diseases caused by plant disruptors carrying diseases, namely Phytopthora sp. Colletotrichum sp. Curvularia sp. Bipolaris sp. and Pestalotiopsis sp. the symptoms of the disease are leaf blight, black spots, leaf spots, and brown spots due to the influence of irregular weather factors. This study was conducted at the Laboratory of Pests, Diseases and Microbial Biotechnology (LAPDiM) and at the kor hill field of the Faculty of Fisheries and Food Science, Universiti Malaysia Terengganu on September 13-21, 2023. Observations of disease symptoms were made in the bukit kor permaculture area of Universiti Malaysia Terengganu. Data collection was done using descriptive qualitative method, looking at the cause of the disease, the level of attack and the symptoms caused. Keywords: Bipolaris. Colletotrichum . Curvularia . Pestalotiopsis, PhytopthoraINTISARI Permakultur merupakan salah satu jenis sistem pertanian yang membutuhkan proses desain tertentu untuk menjadikan sistem pertanian tersebut lebih berkelanjutan. Tanaman di area permakultur terserang penyakit yang disebabkan oleh organisme pengganggu tanaman pembawa penyakit yaitu Phytopthora sp. Colletotrichum sp. Curvularia sp. Bipolaris sp. dan Pestalotiopsis sp. gejala penyakit yang ditimbulkan berupa hawar daun, bintik hitam, bercak daun, dan bintik coklat dikarenakan pengaruh faktor cuaca yang tidak beraturan. Penelitian ini dilakukan di Laboratorium Hama, Penyakit dan Bioteknologi Mikroba (LAPDiM) dan di lahan Bukit Kor Fakultas Perikanan dan Ilmu Pangan, Universiti Malaysia Terengganu pada 13-21 September 2023. Pengamatan gejala penyakit dilakukan di kawasan permakultur Bukit Kor Universiti Malaysia Terengganu. Pengumpulan data dilakukan dengan metode deskriptif kualitatif, melihat penyebab penyakit, tingkat seangan, dan gejala yang ditimbulkan. Kata kunci: Bipolaris. Colletotrichum . Curvularia . Pestalotiopsis, Phytopthora